1822, By-Laws, Rules and Regulations of the…Company for Erecting a Permanent Bridge over the River Schuylkill, at 89, Rules and Regulations, pt. 14. - (:unkn) unknown (General Publisher, 1822)
No guns or other firearms shall be discharged on or near the bridge. And the toll collectors and watchmen are hereby authorized and required to take every legal measure to bring offenders to justice, who, in violation of this regulation and the laws of the Commonwealth, thus annoy passengers and endanger the bridge. A uitable reward will be given, when such offenders are convicted as the law directs.
--
Keywords: DISCHARGE